2012
DOI: 10.1007/s10549-012-2202-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Studies (GWAS) breast cancer susceptibility loci in Arabs: susceptibility and prognostic implications in Tunisians

Abstract: Genome-wide Association Studies (GWAS) revealed novel genetic markers for breast cancer susceptibility. But little is known about the risk factors and molecular events associated with breast cancer in Arab Population. Therefore, we designed a broad study to investigate the susceptibility and prognostic implications of the GWAS breast cancer loci in the Tunisian population. In a cohort of 640 unrelated patients with breast cancer and 371 healthy control subjects, we characterized the variation of 9 single nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 39 publications
5
52
0
Order By: Relevance
“…In total, 18 studies involving 44,820 cases and 58,316 controls met the inclusion criteria and were used in pooled analyses (Antoniou et al, 2008;Garcia-Closas et al, 2008;Li et al, 2009;Mcinerney et al, 2009;Gorodnova et al, 2010;Latif et al, 2010;Liang et al, 2010;Tamimi et al, 2010;Campa et al, 2011;Han et al, 2011;Slattery et al, 2011;Harlid et al, 2012;Shan et al, 2012;Mizoo et al, 2013;Ottini et al, 2013;Chen et al, 2014;Elematore et al, 2014). The primary features of these investigations are shown in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In total, 18 studies involving 44,820 cases and 58,316 controls met the inclusion criteria and were used in pooled analyses (Antoniou et al, 2008;Garcia-Closas et al, 2008;Li et al, 2009;Mcinerney et al, 2009;Gorodnova et al, 2010;Latif et al, 2010;Liang et al, 2010;Tamimi et al, 2010;Campa et al, 2011;Han et al, 2011;Slattery et al, 2011;Harlid et al, 2012;Shan et al, 2012;Mizoo et al, 2013;Ottini et al, 2013;Chen et al, 2014;Elematore et al, 2014). The primary features of these investigations are shown in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In the end, 14 articles were found to satisfy the inclusion criteria and were included in the meta-analysis [21][34]. These articles involved a total of 44,283 cases and 55,756 controls, of which 5,170 cases and 5,589 controls were Chinese [25][27], [32], and the remaining 39,113 cases and 50,167 controls were of mixed ethnicity (>95% Caucasian) [21][24], [28][31], [33], [34]. In one study [22], 95.6% of cases and 96.7% of controls were European, while 4.4% of cases and 3.3% of controls were Asian.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies included in the meta-analysis demonstrate that rs13281615 polymorphisms can interact with environmental factors to modulate BC risk [23][27], [29], [32], [34]. In fact, rs13281615 polymorphisms were not found to interact with BRCA1 or BRCA2 in BC risk, though only one study [30] examined the possibility of such genetic interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The rs12443621 SNP of the TNRC9 gene (also named TOX3) is located at chromosome 16q12. The function of TNRC9 is still unclear, but a previous study conducted by Shan et al, (2012) has reported that TNRC9 down-regulates BRCA1 expression through altering the methylation status of its promoter and promotes breast cancer aggressiveness. Other risk factors for breast cancer may include population differences that vary by ethnicity, family history, menopausal status and each of estrogen receptor (ER), progesterone receptor (PR), or human epidermal growth factor receptor 2 (HER2) tumor statuses.…”
Section: Discussionmentioning
confidence: 99%